7 Sunday strategy affects match day +2 salivary cortisol and sIgA response following saturday matches through an english championship football club season. (December 2018) - Dunbar, J; King, M; Haslam, C; Nevill, A; Warrington, G
Abstract : The measurement of salivary biomarkers has become popular in professional sport, in an attempt to monitor the stress responses associated with training, competition, and other related lifestyle factors. Using a 'Point of Care' platform, giving results within minutes of sample collection in the professional football environment, the aim is to provide coaching staff with 'readiness to train' data relating to individual players or the squad as a whole. At this club, after a Saturday match where there is no game until the following Saturday, players do not report to training until Monday Morning. However, if the next game is midweek, players are required to report to training on Sunday morning for recovery protocols. Salivary samples were collected for evaluation of sIgA and cortisol from 26 players (age 24.1±2.9 y, body mass 78.7±6.5 kg, stature 1.81±0.07) in a Championship football club squad at 09:00 on the Monday following a Saturday Match throughout the 2017–2018 season. In total 19 time-points were analysed; 11 where players reported in on a Sunday and 8 where players had the Sunday off from training post-match. All saliva samples were analysed at the training ground using Soma dual sIgA/Cortisol LFDs read with a Soma Cube LFD Reader to give rapid quantitative values for sIgA and cortisol. sIgA was seen to be variable, both within (CV 53.8%) and between players (CV 62.1%), as was the cortisol response (within CV 53.2% and between players CV 65.3%). Multi-Level regression analysis revealed a highly significant quadratic effect in sIgA due to 'weeks' throughout the season (the intercept at zero weeks was 187 µg/mL initially increasing at the early weeks, peaking mid-season then declining significantly towards the end of the season). Where players reported to training on Sunday, the Monday sIgA response was 60 µg/mL lower than when Sundays were spent at home. The Model for cortisol response showed a highly significant linear increase throughout the season. However, the impact of reporting for recovery training on Sunday had a significant impact on Monday cortisol, changing from 4.9 (0.8) nM when they did report in on Sunday to 9.6 (0.6) nM when they did not. Such biomarker responses may have important implications and practical applications for the planning of recovery strategies for subsequent professional football matches.